2011
DOI: 10.1177/039463201102400419
|View full text |Cite
|
Sign up to set email alerts
|

Psychophysical Distress and Alexithymic Traits in Chronic Fatigue Syndrome with and without Comorbid Depression

Abstract: Patients with Chronic Fatigue Syndrome (CFS) often report a comorbid depressive disorder. Comorbid depression may negatively influence the long-term outcome of CFS therefore it must be correctly diagnosed and treated. The aim of the present study is to provide a clinical and psychometric assessment of CFS patients with and without depressive features. A comparative analysis between 57 CFS subjects (CDC, 1994), 17 of whom with a comorbid depression, and 55 matched healthy volunteers was assessed to evaluate the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 28 publications
0
4
0
Order By: Relevance
“…Using a conservative p ‐value, no difference was found between CFS and ES in TAS‐20 measures, the only exception being the scale difficulty describing feelings (DDF) where CFS patients reported less difficulty compared to ES patients. Previous studies indicate that patients with CFS report more difficulties in identifying feelings than HCs (Sepede et al ., ; van de Putte et al ., ), and even after adjusting for multiple comparisons, this study confirmed previous results. Moreover, the results of this study indicate that emotional awareness capacity might be hampered in CFS when a performance‐based measure such as the LEAS is used (Oldershaw et al ., ).…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…Using a conservative p ‐value, no difference was found between CFS and ES in TAS‐20 measures, the only exception being the scale difficulty describing feelings (DDF) where CFS patients reported less difficulty compared to ES patients. Previous studies indicate that patients with CFS report more difficulties in identifying feelings than HCs (Sepede et al ., ; van de Putte et al ., ), and even after adjusting for multiple comparisons, this study confirmed previous results. Moreover, the results of this study indicate that emotional awareness capacity might be hampered in CFS when a performance‐based measure such as the LEAS is used (Oldershaw et al ., ).…”
Section: Discussionmentioning
confidence: 96%
“…However, only difficulties of identifying feelings remained significant after controlling for age, gender, anxiety and depression. In a similar vein, depressed and non‐depressed adult CFS patients were found to report more impairment in identifying feelings compared to healthy controls (Sepede, Racciatti, Gorgoretti et al ., ). Other studies indicate that CFS patients report more difficulties identifying feelings compared to “minor health conditions” (e.g., the common cold) (Vanheule, Vandenbergen, Verhaeghe & Desmet, ), but, in contrast, less difficulties compared to patients with rheumatoid arthritis (Wood & Wessely, ).…”
Section: Introductionmentioning
confidence: 97%
“…In a model proposed by Goldbacher et al [54], psychological factors may contribute to the pathogenesis of MetS via physiological as well as behavioral mediating pathways. Several studies confirm that alexithymia is related to physical [55] and psychological distress [56], and directly associated with hyperarousal, sympathetic over-activity [57], and altered immune responses [58]. It may represent a personality marker of stress sensitivity or a vulnerability marker of stress, facilitating both unhealthy behaviors and inflammatory processes [57].…”
Section: Discussionmentioning
confidence: 96%
“…In this study, we assessed the effects of regular practice of isometric yoga on HADS-D (depressive symptoms), HADS-A (anxiety), and TAS-20 (alexithymia) and found that isometric yoga exclusively improved HADS-D scores, suggesting an improvement in depressive symptoms by regular practice of yoga. As comorbid depression has been demonstrated to increase the level of psychophysical distress in patients with CFS [73], the seated isometric yoga-induced reduction in depressive symptoms must be beneficial for them.…”
Section: Discussionmentioning
confidence: 99%